2020
DOI: 10.1109/access.2020.2985254
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Agent Microgrid Management System for Single-Board Computers: A Case Study on Peer-to-Peer Energy Trading

Abstract: Smart grids concept benefits and leverage distributed management systems while allowing its players to actively participate in the smart grid. This paper merges the concepts of microgrid and transactive energy. The proposed model is tested in an office building with multiple tenants. An agentbased platform, running in single-board computers, for microgrid intelligent management with a peer-topeer energy transaction model is proposed in this paper. This paper describes the peer-to-peer transaction auction model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…P2P can be used in local electricity market models incorporating both energy trading and uncertainty trading simultaneously to match the forecast power with demand having time flexibility and the uncertain power [48,49]. P2P transaction auction models and the deployment of platforms buildings will emerge economic and control mechanisms that allows the dynamic balance of supply and demand across the electrical infrastructure [50], with optimised real‐time scheduling and trading prices [51].…”
Section: Future Grid Architecturementioning
confidence: 99%
“…P2P can be used in local electricity market models incorporating both energy trading and uncertainty trading simultaneously to match the forecast power with demand having time flexibility and the uncertain power [48,49]. P2P transaction auction models and the deployment of platforms buildings will emerge economic and control mechanisms that allows the dynamic balance of supply and demand across the electrical infrastructure [50], with optimised real‐time scheduling and trading prices [51].…”
Section: Future Grid Architecturementioning
confidence: 99%
“…Another application with EVs to offers services for the network operator was presented by the authors of [17], who proposed the charging management of EVs to reduce the photovoltaic (PV) curtailment. Also, Peer-to-Peer (P2P) models have been proposed as another promising model for transacting electricity in LEM [18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [17] addressed the charging coordination for EVs but the possibility of negotiating local electricity was not considered. The authors of [18] showed a local market for electricity in a P2P model but did not include EVs.…”
Section: Introductionmentioning
confidence: 99%
“…MG's consumers can be prosumers, who can both consume and generate energy [4]. Purchasing and selling power between participants in the energy industry is called power trading, which is developed based on the "Peer to Peer (P2P) economy" concept [5] which is a decentralized model whereby two individuals interact to buy/sell energy with each other. Unlike the decentralized mode, in the centralized method the MGs are not directly related to each other.…”
Section: Introductionmentioning
confidence: 99%